Stabilisasi ekonomi di era revolusi : Studi atas kebijakan fiskal - shofa, abdullaah (Maliki Interdisciplinary Journal, 2025)
This article discusses the budget policy implemented by the Indonesian government in 1949 in an effort to stabilize the economy after independence. In difficult economic conditions due to the war of independence and high inflation, the government implemented a balanced budget policy to reduce budget deficits and suppress inflation. State revenues, especially taxes, were increased through changes in the taxation system to save on urgent needs, including stabilizing the prices of basic goods. This policy demonstrated the importance of careful budget planning in maintaining economic stability amidst the crisis. Despite facing various obstacles, the 1949 budget policy was an important step in the history of Indonesian economic management. Limited resources can be improved through strategic financial management, thereby creating the basis for more sustainable economic development in the years to come